The effect of political institutions on the interplay between banking regulation and banks’ risk - Dutra, T. M.; Teixeira, J. C. A.; Dias, J. C. (Journal of Banking Regulation, 2023)
This paper examines whether the influence of banking regulation on banks’ risk is channeled through the quality of political institutions. As banking regulatory factors, we consider capital stringency, activity restrictions and supervisory power. The overall effect of banking regulation on banks’ risk is conditional on the quality of political institutions. Activity restrictions and capital stringency have a statistically significant positive effect on banks’ risk. This effect is mitigated by better political institutions. In contrast, stringent supervisory power tends to reduce banks’ risk, and better political institutions reinforce this effect. The results are robust for alternative estimation methods and risk measures.